2022
DOI: 10.3390/s22124513
|View full text |Cite
|
Sign up to set email alerts
|

Directed Functional Coordination Analysis of Swallowing Muscles in Healthy and Dysphagic Subjects by Surface Electromyography

Abstract: Swallowing is a complex sequence of highly regulated and coordinated skeletal and smooth muscle activity. Previous studies have attempted to determine the temporal relationship between the muscles to establish the activation sequence pattern, assessing functional muscle coordination with cross-correlation or coherence, which is seriously impaired by volume conduction. In the present work, we used conditional Granger causality from surface electromyography signals to analyse the directed functional coordination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…Furthermore, this device conforms to the international diagnostic EMG standard (IEC 60601-2-40) [ 170 ]. The Ultium EMG (Noraxon USA, Inc., Scottsdale, AZ, USA) is also used in the studies of masticatory muscles [ 128 , 171 , 172 , 173 ]. It is worth noting that this sEMG can examine different muscles of the body and is not dedicated to a specific group [ 170 ].…”
Section: Surface Electromyography In Dentistry—presentmentioning
confidence: 99%
“…Furthermore, this device conforms to the international diagnostic EMG standard (IEC 60601-2-40) [ 170 ]. The Ultium EMG (Noraxon USA, Inc., Scottsdale, AZ, USA) is also used in the studies of masticatory muscles [ 128 , 171 , 172 , 173 ]. It is worth noting that this sEMG can examine different muscles of the body and is not dedicated to a specific group [ 170 ].…”
Section: Surface Electromyography In Dentistry—presentmentioning
confidence: 99%
“…Within the swallowing theme, Ye Lin et al used conditional Granger causality from surface EMG signals to analyze the directed functional coordination between different swallowing muscles in healthy and dysphagia patients swallowing water, saliva, and yoghurt [ 3 ]. The study indicated that the analysis of functional coordination supplied relevant information for evaluating motor control synergy and provided a step towards identifying new and robust biomarkers for the early detection of dysphagia.…”
Section: Overview Of Contributionmentioning
confidence: 99%
“…1 Furthermore, dysphagia among older adults has evolved into a major medical and social problem, such as the increase in medical costs related to the treatment of dysphagia including aspiration pneumonia. 2,3 Videofluorographic swallowing study (VFSS), 4 videoendoscopic examination of swallowing (VE), 4 electromyogram, 5 manometry, 6 and swallowing computed tomography (CT) 7 are some of the tests used to pathologically diagnose dysphagia. Among these tests, VFSS and VE are the most commonly performed.…”
Section: Introductionmentioning
confidence: 99%
“…Videofluorographic swallowing study (VFSS), 4 videoendoscopic examination of swallowing (VE), 4 electromyogram, 5 manometry, 6 and swallowing computed tomography (CT) 7 are some of the tests used to pathologically diagnose dysphagia. Among these tests, VFSS and VE are the most commonly performed.…”
Section: Introductionmentioning
confidence: 99%